THE PREVALENCE AND COMORBIDITY OF DEATH ANXIETY AND PSYCHOLOGICAL DISTRESS IN PAKISTANI POPULATION DURING COVID-19 PANDEMIC - Muneeba Shakil; Farzana Ashraf; Shahnila Tariq; Alia Asmat; Amina Muazzam; Naima Hassan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This study was carried out to determine the prevalence and comorbidity of death anxiety and psychological distress in the Pakistani Population During the COVID-19 Pandemic. In this cross-sectional study, 468 participants between the ages of 16 to 55 years (M= 32.15, SD+9.01) were recruited online through convenient sampling via google form from September to October 2020. Chi-square test of association was performed to calculate the association between death anxiety and psychological distress across gender, ages, marital statuses, and family system. Findings revealed a 1% to 2% prevalence of severe psychological distress at a moderate level of death anxiety across all measurement dimensions. Women reported low death anxiety at a moderate level of psychological distress, whereas this prevalence was steady for men. Psychological distress was linear for young and older adults, whereas fluctuating for adolescents. High death anxiety was reported at a moderate level of psychological distress, which declined at a severe psychological distress level. Besides, unmarried participants reported more death anxiety at moderate and severe psychological distress levels than their married counterparts. Participants from the joint family system reported high death anxiety at a moderate psychological distress level. Contrary to this, at a severe level of psychological distress, more death anxiety was reported from participants living in the nuclear family system. This study would help develop appropriate interventions to improve vulnerable groups' mental health during the COVID-19 pandemic.